DAYA ANTIBAKTERI EKSTRAK BUAH BELIMBING WULUH (Averrhoa bilimbi Linn) TERHADAP Methicillin Resistant Staphylococcus aureus - Ricky Alexander Chandra; Rina Yunita; Dian Dwi Wahyuni; Dwi Rita Anggraini (Kelompok Ilmiah Hippocrates Fakultas Kedokteran Universitas Udayana, 2018)
Background: Staphylococcus aureus become resistant against several group of antibiotics such as penicillins, aminoglycosides, and quinolones. Current world concern is antibiotic resistance to Methicillin Resistant Staphylococcus aureus (MRSA) because these cases are still increasing. The high incidende of infectious disease and antibiotic resistance become a challenge to find out new, effective, alternative antibiotics. Bilimbi fruit contains bioactive compounds such as flavonoids, saponins, and tannins. The bioactive compounds are proven as natural antibacterial. Aims: To determine antibacterial activity of bilimbi fruits extract against MRSA. Methods: Bilimbi fruit were collected from a garden at Tanjung Mulia, Medan. Bilimbi fruits were extracted by using maceration method with 96% ethanol as solvent. Antibacterial activity was tested with well-diffusion method. Wells are made by using a sterile cork borer with 6 mm in diameter. Treatments are divided into 6 groups, 6,25%, 12,5%, 25% and 50% bilimbi fruits extract, positive control (chloramphenicol 2% ointment) and negative control (dimethylsulfoxide). Each group is repeated four times. Results: Average inhibitory zone diameter concentration of 6.25% is 15.150 ± 0,310 mm, concentration of 12.5% ??is 18.075 ± 0,309 mm, concentration of 25% is 20.225 ± 0,680 mm, and concentration of 50% is 24.375 ± 2,209 mm. Inhibitory zone of each group is analyzed with Kruskal-Wallis test. Results showed all groups have significant differences. Conclusions: Bilimbi fruits ethanolic extract had antibacterial activity against MRSA. The best concentration of bilimbi fruits extract to inhibit the growth of MRSA is 50%.